Multi-user synchronization in DS-CDMA - Li, Kwok Hung. (2008)
Spread-spectrum (SS) communications; with its inherent interference rejection and multiple- access capability, has become a bandwidth-efficient and popular technique for use in multi-user systems. In particular, direct-sequence code-division multiple access (DS- CDMA) can potentially accommodate more users than other multiple-access techniques. However, the efficiency of DS-CDMA systems depends heavily on the synchronization capability of the receiver. The receiver must maintain continuous synchronization be- tween the incoming DS/SS signal and the locally generated pseudo-noise (PN) codes. This research project, entitled Multi-User Synchronization in DS-CDMA, studies three important synchronization issues of a DS-CDMA system. They are all related to PN code tracking for multi-user wireless communications.